Photoresists: Access to Disparate Soft Matter Materials by Curing with Two Colors of Light (Adv. Mater. 8/2019). Issue 8 (19th February 2019) - Bialas, Sabrina; Michalek, Lukas; Marschner, David E.; Krappitz, Tim; Wegener, Martin; Blinco, James; Blasco, Eva; Frisch, Hendrik; Barner‐Kowollik, Christopher
Abstract : When two different colors of light illuminate an advanced truly wavelength‐orthogonal photoresist, the color of light alone determines the material properties of the cured system, opening unique opportunities in the realm of multi‐material fabrication and printing. This phenomon is investigated by James Blinco, Eva Blasco, Hendrik Frisch, Christopher Barner‐Kowollik, and co‐workers in article number1807288 .